Perceptions of Africa’s Role in the Western Indo-Pacific: An Indian Perspective (The Strategic Review for Southern Africa, 2022)
For over a decade, the Indo-Pacific has emerged as a new construct – an intellectual device – to interpret and comprehend the changing geopolitical dynamics in Asia and beyond. Besides, it is aptly viewed as a strategy and policy by powers within this region and outside, which assists them in identifying and safeguarding their national interests in an evolving situation. Among the diverse players, there is a clear division between those states such as the Quad powers (the US, India, Japan, and Australia) that support the concept, and those states such as China and Russia that oppose it. This gives the ongoing debate on the Indo-Pacific clear ideological and political colour. Is this discussion then only about China's rise and behaviour and how it needs to be addressed, or does it relate to the larger issue of an inclusive, equitable, and multipolar order that promotes peace, security, and prosperity of all states covered by this concept, including those in Africa?